The Life Satisfaction Approach to Environmental Valuation - Bruno S. Frey; Simon Luechinger; Alois Stutzer (University of Basel, Center of Business and Economics (WWZ), 2009)
In many countries environmental policies and regulations are implemented to improve environmental quality and thus individuals' well-being. However, how do individuals value the environment? In this paper, we review the Life Satisfaction Approach (LSA) representing a new non-market valuation technique. The LSA builds on the recent development of subjective well-being research in economics and takes measures of reported life satisfaction as an empirical approximation to individual welfare. Micro-econometric life satisfaction functions are estimated taking into account environmental conditions along with income and other covariates. The estimated coefficients for the environmental good and income can then be used to calculate the implicit willingness-to-pay for the environmental good.
Keywords: Q51; I31; D61; Q53; 330; life satisfaction approach; subjective well-being; non-market valuation; costbenefit analysis; air pollution; Umweltbelastung; Umweltschutz; Kosten-Nutzen-Analyse; Zufriedenheit; Lebensqualität; Zahlungsbereitschaftsanalyse; Theorie